An Act for the Better Securing the Government by Disarming Papists and Reputed Papists, 1 W. & M., Sess. 1, ch. 15 (Eng. 1688). See also 4 Commentaries on the Laws of England 55 (1769) - (:unkn) unknown (General Publisher, 1689)
Prohibition on Catholics from possessing firearms and ammunition unless an oath renouncing their faith was taken. Catholics who did not attend Church of England services could not keep arms within their home. Used by the Court to define "keeping arms" as outside of militia service.
--
Keywords: RELIGIOUS RESTRICTION